2020
DOI: 10.2147/vhrm.s266582
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pattern of Cardiac Diseases and Co-Existing Morbidities Among Newly Registered Cardiac Patients in an Adult Cardiac Referral Clinic of Hawassa University Comprehensive Specialized Hospital, Southern-Ethiopia</p>

Abstract: Background: Currently, cardiovascular diseases (CVDs) are rising in the world and require great concern because the consequences are not only morbidity and mortality, but also a high economic burden. However, the pattern of CVDs in Ethiopia is not well known. Therefore, this study aimed to describe CVD and co-existing morbidities among newly registered cardiac patients in Hawassa University Comprehensive Specialized Hospital. Methods: A retrospective cross-sectional study was conducted from January 1 to Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…It is also similar to the study conducted in SSA. [5,10,12] Hypertensive heart disease was the fourth commonest (13%) type of heart disease which is similar the study done in Hawassa (12.5%),but lower as compared to the nding of the previous study done at JUMC (24%) [5,14].Study from other developing countries showed HHD has become the rst leading cause of heart disease. [10,11] Hypertension was found to be the most common comorbidity associated with cardiac disease(21.3%) which similar to other studies done in Ethiopia.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It is also similar to the study conducted in SSA. [5,10,12] Hypertensive heart disease was the fourth commonest (13%) type of heart disease which is similar the study done in Hawassa (12.5%),but lower as compared to the nding of the previous study done at JUMC (24%) [5,14].Study from other developing countries showed HHD has become the rst leading cause of heart disease. [10,11] Hypertension was found to be the most common comorbidity associated with cardiac disease(21.3%) which similar to other studies done in Ethiopia.…”
Section: Discussionsupporting
confidence: 68%
“…On the other hand, the prevalence of RHD is comparable to the study conducted at southern Ethiopia which was 29.7% [14] and other studies done in different parts of Ethiopia but slightly lower than the same study done 12years back at JUMC which showed 32.8% [5]. The most common pattern of valvular lesion is combined mitral stenosis with mitral regurgitation (39.6%) while isolated MR and MS were found to be equal 13(22.4%) each.…”
Section: Discussionsupporting
confidence: 65%
“…In young adults RHD remain to be a common diagnosis similarly to the findings form a study done in Nigeria [ 24 ], Cameroon [ 22 ], rural Tanzania by Dominick et al [ 7 ]. However, on the contrary studies done in Ethiopia [ 31 , 32 ], found RHD to be the commonest overall echocardiographic diagnosis. These differences can be explained by the tertiary/urban nature of our study setting while those in Cameroon were conducted in rural settings where rheumatic heart disease is most prevalent.…”
Section: Discussionmentioning
confidence: 82%